2011
DOI: 10.3892/or.2011.1232
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of hyperthermia and dendritic cell immunotherapy for squamous cell carcinoma

Abstract: Abstract. the aims of this study were to explore the feasibility of a novel combination therapy comprising hyperthermia (Ht) and dendritic cell (Dc) application for squamous cell carcinoma (scc), and to optimize the conditions of this therapy. In vitro, the correlation between maturation of Dcs by co-culture with sccVII cells and Ht was investigated. DCs did not mature in simple HT (43˚C for 30 min) with sccVII cells. on the other hand, Dc maturation occurred in additional mild HT (mHT: 41˚C for 30 min) with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Only when tumor cells and immature DCs are both under sequential hyperthermia treatment, can the immature DCs be effectively activated. This result suggests that DCs’ maturation not only depends on danger signals with HSPs but also on hyperthermia itself independently ( 61 ). Further studies proposed that fever-range hyperthermia promote DCs from a quiescent status to an activated status by promoting the metabolic reprogramming in them ( 62 , 63 ).…”
Section: Hyperthermia Enhanced the Immune Response In Multiple Stepsmentioning
confidence: 99%
“…Only when tumor cells and immature DCs are both under sequential hyperthermia treatment, can the immature DCs be effectively activated. This result suggests that DCs’ maturation not only depends on danger signals with HSPs but also on hyperthermia itself independently ( 61 ). Further studies proposed that fever-range hyperthermia promote DCs from a quiescent status to an activated status by promoting the metabolic reprogramming in them ( 62 , 63 ).…”
Section: Hyperthermia Enhanced the Immune Response In Multiple Stepsmentioning
confidence: 99%
“…23,24 For dendritic cells (DCs), which present antigens to adaptive immune cells, hyperthermia can enhance their proliferation, maturation, and antigen presentation. [25][26][27][28][29][30] Moreover, natural killer cells are activated and show elevated cytotoxicity and recruitment to tumor sites on heating, causing increased tumor cell recognition by natural killer cells. 31,32 Adaptive immune cells can also be targeted by heat.…”
Section: Mechanisms Of Hyperthermia Combined With Immunotherapymentioning
confidence: 99%
“…In vitro heating accelerates DC maturation as demonstrated by up-regulation of both CD86 and MHC class II (60, 61, 67). In vivo studies have also shown that up-regulation of both MHC class II and CD86 molecules on the surface of DCs from mice treated with whole body hyperthermia (61, 68). Additionally, hyperthermia in combination with other treatments including ionizing radiation (69), magnetic nanoparticles (70, 71), radiofrequency ablation (72) and vaccination (73, 74) results in enhanced DC function.…”
Section: Effects Of Mild Hyperthermia On Dcsmentioning
confidence: 99%